Mixed Sweeteners Supplemented with Chromium Picolinate (CrPic) Improved Some Diabetes-Related Markers and Complications in a Type 2 Diabetic Rat Model - Ekomobong Inyang; Ifeoma Irene Ijeh; Sunday Oyedemi (Nutraceuticals)
Several studies have explored the effects of single or binary mixtures of sweeteners on both healthy individuals and those with diabetes. However, there is limited research on the impact of a combination of four sweeteners supplemented with dietary minerals. Steviol glycosides, extracted from Stevia rebaudiana, offer a zero-calorie sweetness that exerts minimal influence on blood glucose levels. When combined with other sweeteners, they can reduce the required quantity of each component thus mitigating the potential side effects. Furthermore, the incorporation of chromium picolinate into sweeteners may enhance insulin sensitivity and glucose metabolism and diminish insulin resistance in both diabetic and non-diabetic individuals. This study aimed to evaluate the effects of commercial mixed sweeteners (acesulfame-K, sucralose, sorbitol, and steviol glycoside) supplemented with chromium picolinate (MSSC) on diabetes-related markers and complications in healthy and type 2 diabetic rats (T2D). Over six weeks, diabetic rats received daily oral administration of MSSC at a standard dosage. The results demonstrated that MSSC significantly reduced weight loss in diabetic rats, lowered fasting blood glucose levels, enhanced hexokinase activity, and improved pancreatic antioxidative capacities. Additionally, MSSC treatment led to notable reductions in serum triglycerides, cholesterol, malondialdehyde (MDA), and LDL cholesterol levels. The treatment also modulated specific renal function parameters, and moderately reversed the necrotic architectures of the liver and pancreatic β cells. These results indicate that long-term administration of MSSC may alleviate certain diabetic complications without adverse effects on non-diabetic individuals. Further clinical studies are strongly recommended to evaluate the safety and efficacy of MSSC in diverse populations.